Elevating urban landscapes: architectural innovations for green roofs and vertical gardens in Malaysian cities - Ma'rof, Aini Azeqa; Miranda, Timothy; Mohd Noor, Mohd Zairul (Human Resource Management Academic Research Society, 2024)
This research investigates innovative architectural design strategies to promote green roofs and vertical gardens in Malaysian urban centers. Despite their environmental and energy- saving benefits, adoption is limited due to public awareness gaps, regulatory barriers, and climate-related challenges. This study aims to bridge these gaps by developing climate- resilient design frameworks and implementation incentives, focusing on suitable plant selection and maintenance for Malaysia's tropical climate. By addressing deficiencies in current green roof maintenance, the research seeks to provide practical architectural design guidelines that facilitate the effective integration of green infrastructure into urban architecture. Expected results include enhanced architectural design strategies enabling broader implementation of green roofs and vertical gardens, contributing to sustainable urban environments. The contribution to society involves fostering greener urban landscapes, improving air quality, reducing energy consumption, and mitigating urban heat islands, paving the way for a more sustainable and livable future for Malaysian urban cities.